2023
DOI: 10.2174/1568009623666230215142941
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial Chemoembolization Followed by Hepatic Arterial Infusion Chemotherapy Combined a Tyrosine Kinase Inhibitor for Treatment of Large Hepatocellular Carcinoma

Abstract: Objective: Evaluate the efficacy and safety of transarterial chemoembolization (TACE) sequential with hepatic arterial infusion chemotherapy (HAIC) and a tyrosine kinase inhibitor (TKI) for unresectable large hepatocellular carcinoma (HCC). Methods: Patients with HCC size > 70 mm were included. They received 1-3 cycles of TACE and sequential HAIC every 3-6 weeks for 2-6 cycles, with each cycle given over a period of 48 hours (oxaliplatin plus fluorouracil/leucovorin). Patients also received sorafenib or l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The ORR and DCR in the TACE-HAIC group were higher than those in the HAIC group (65.6% vs. 53.7% and 90.6% vs. 78.0%, respectively), although the differences were not statistically significant. This may be explained as follows: TACE promotes tumor cell necrosis, intertissue ion transport, and interstitial hypertension changes, which together contribute to the distribution of chemotherapeutic drugs ( 16 , 17 ). TACE can block the tumor’s main blood vessels, whereas HAIC is more conducive to the control of tumors with deficient blood supply ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ORR and DCR in the TACE-HAIC group were higher than those in the HAIC group (65.6% vs. 53.7% and 90.6% vs. 78.0%, respectively), although the differences were not statistically significant. This may be explained as follows: TACE promotes tumor cell necrosis, intertissue ion transport, and interstitial hypertension changes, which together contribute to the distribution of chemotherapeutic drugs ( 16 , 17 ). TACE can block the tumor’s main blood vessels, whereas HAIC is more conducive to the control of tumors with deficient blood supply ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained as follows: TACE promotes tumor cell necrosis, intertissue ion transport, and interstitial hypertension changes, which together contribute to the distribution of chemotherapeutic drugs ( 16 , 17 ). TACE can block the tumor’s main blood vessels, whereas HAIC is more conducive to the control of tumors with deficient blood supply ( 17 ). The combination of TACE and HAIC integrates the advantages of both to achieve better tumor control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination therapy for TACE-refractory HCC has been explored ( 18 ). For example, several studies have shown that the combination of HAIC plus TKI resulted in better survival outcomes compared to TKI or HAIC monotherapy ( 32 , 35 , 36 ). The OS reported in our study was 9.0 months, which was lower compared to previous clinical trials ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%